Introduction of an Al Seed Layer for Facile Adsorption of MoCl5 during Atomic Layer Deposition of MoS2. Issue 15 (26th May 2020) - Ahn, Wonsik; Lee, Hyangsook; Cho, Yeonchoo; Byun, Kyung-Eun; Kim, Hoijoon; Leem, Mirine; Lee, Heesoo; Park, Taejin; Lee, Eunha; Shin, Hyeon-Jin; Kim, Hyoungsub
Abstract : A low‐temperature one‐step growth method for few‐layer MoS2 using an atomic layer deposition scheme with MoCl5 and H2 S precursors is systematically studied by introducing an ultrathin Al seed layer. First, to optimize the deposition conditions, the effects of the deposition (200–420 °C) and MoCl5 canister (100–160 °C) temperatures on the MoS2 growth behavior are investigated. On the SiO2 surface, increasing the deposition temperature reduces the growth rate while favoring more lateral growth. However, an increase in the MoCl5 sublimating temperature, which is beneficial to improve the film quality, sharply reduces the growth rate, probably owing to the pronounced self‐etching effect of MoCl5 . To compensate for the reduced deposition rate while maintaining the MoS2 quality, an ultrathin Al seed layer (≈5 nm) is introduced, which promotes the surface adsorption of MoCl5 molecules at an early growth stage according to density functional theory calculations. Thus, a polycrystalline mono‐to‐bilayer MoS2 film with negligible amounts of residual contaminants (particularly Cl and Al) is successfully synthesized using the proposed Al seeding approach. Abstract : For a low‐temperature one‐step growth of MoS2 using an atomic layer deposition scheme with MoCl5 and H2 S precursors, an Al seed layer is introduced. It promotes the surface adsorption of MoCl5 and produces a mono‐to‐bilayer MoS2 film with negligible amounts of residual contaminants.